HEALTHY AND BALANCED NUTRITION FOR INDIVIDUALS WITH DOWN SYNDROME - Komilova Dildora Alisherovna (Web of Journals Publishing, 2024)
Healthy and balanced nutrition is vital for individuals with Down syndrome. Proper nutrition ensures the proper intake of essential nutrients and prevents long-term health complications. This information sheet encompasses dietary recommendations for children and adults with Down syndrome.
Keywords: Down syndrome, respiratory, hypotonia, atrophy, lactation, breastfeeding, atrophy, sucking, feeding, breastfeeding, chest.